2019
DOI: 10.1038/s41467-018-08195-6
|View full text |Cite
|
Sign up to set email alerts
|

Ocean temperature impact on ice shelf extent in the eastern Antarctic Peninsula

Abstract: The recent thinning and retreat of Antarctic ice shelves has been attributed to both atmosphere and ocean warming. However, the lack of continuous, multi-year direct observations as well as limitations of climate and ice shelf models prevent a precise assessment on how the ocean forcing affects the fluctuations of a grounded and floating ice cap. Here we show that a +0.3–1.5 °C increase in subsurface ocean temperature (50–400 m) in the northeastern Antarctic Peninsula has driven to major collapse and recession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…EN4 is a global, quality-controlled, objectively-analyzed, dataset of observed potential temperature and salinity profiles which has been used extensively (e.g., Prieto et al, 2015;Yang et al, 2016;Zunino et al, 2017;Chafik et al, 2019;Etourneau et al, 2019). It combines data from all types of profiling instruments, including ship-based measurements and ARGO floats, and is available as monthly averages (Good et al, 2013).…”
Section: En4 Datamentioning
confidence: 99%
“…EN4 is a global, quality-controlled, objectively-analyzed, dataset of observed potential temperature and salinity profiles which has been used extensively (e.g., Prieto et al, 2015;Yang et al, 2016;Zunino et al, 2017;Chafik et al, 2019;Etourneau et al, 2019). It combines data from all types of profiling instruments, including ship-based measurements and ARGO floats, and is available as monthly averages (Good et al, 2013).…”
Section: En4 Datamentioning
confidence: 99%
“…The ocean (Etourneau et al, 2019) and atmosphere (Mulvaney et al, 2012;Thomas et al, 2009;Morris and Vaughan, 2003) is already warming along the Antarctic Peninsula. This results in a southward progressing of the annual 2m-air temperatures of -9 • C or -5 • C isotherm, which presents the range of thresholds for the stability of ice shelves suggested by Morris and Vaughan (2003, -9 • C) and Doake (2001, -5 • C), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These records are key to understanding the evolution of climate teleconnections presently impacting Antarctica's ice sheets and sea ice (e.g., Yuan, 2004;Rignot et al, 2019), such as recently shown by geological observations of oceanic forcing of marine-based ice sheets (e.g. Hillenbrand et al, 2017;Etourneau et al, 2019).…”
Section: Ice Sheet Dynamics Under Warmer-than-present Climates Of Thementioning
confidence: 99%
“…There needs to be an emphasis on obtaining, when possible, high resolution records (i.e., orbital to annual) of cryosphere-ocean-atmosphere interactions leading up to and during past deglaciation episodes. These records are key to understanding how past changes in atmospheric circulation influenced the transport of ocean heat to the ice sheet grounding lines (Hillenbrand et al, 2017;Etourneau et al, 2019). They also are important for helping to define the nonlinear or variable ice margin retreat during climate warming, rather than having to assume a simple switch in the ice sheet models between advanced and retreated states.…”
mentioning
confidence: 99%